LITERARY TRANSLATION OF CONDITIONAL SENTENCES IN SPINNER OF THE DARKNESS & OTHER TALES SHORT STORIES - Siti Nur Mariam Mutiara; Ni Luh Putu Setiarini (Universitas Gunadarma, 2025)
Nowadays, many Indonesian literary works are translated into English due to Indonesian authors Internationally acknowledged. One of them is Intan Paramaditha Book entitled Spinner of Darkness & Other Tales. The stories in this book have been translated into English and German. This article aims to show how Conditional Sentences in the stories are being translated into English and what literary translation strategies were used to translate them. This study used a descriptive qualitative method. The Literary translation of conditional sentences and the use of the literary translation strategies are analyzed and described qualitatively. The result of the study showed that conditional sentences are translated into three different types of English conditional sentences. 10% of the data are translated into Conditional sentences type 1, 80% of the data are translated into conditional sentences type 2, and 10% of the data are translated into Conditional sentences type 3. There are three literary translation strategies used to translate conditional sentences; 50% of the data used helper strategy, 30% of the data used adherent strategy and 20% of the data used observer strategy. Thus, the literary translation approach that is mostly used in this study is a biased approach since helper strategy belongs to Biased principal-strategies